2020
DOI: 10.18632/aging.102935
|View full text |Cite
|
Sign up to set email alerts
|

EMMPRIN/CD147 plays a detrimental role in clinical and experimental ischemic stroke

Abstract: Background: Ischemic stroke is a devastating disease, often resulting in death or permanent neurological deficits. EMMPRIN/CD147 is a plasma membrane protein that induces the production of matrix metalloproteinases (MMPs), which contribute to secondary damage after stroke by disrupting the blood brain barrier (BBB) and facilitating peripheral leukocyte infiltration into the brain. Results: CD147 surface expression increased significantly after stroke on infiltrating leukocytes, astrocytes and endothelial cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 51 publications
1
30
0
Order By: Relevance
“…Therefore, the functional interaction between TMPRSS2 and furin is a key factor in determining the level of S protein priming. Other host proteins-such as heat shock protein family A (hsp70) member 5 (HSPA5, also known as GRP78) [43] and CD147 (an inducer of matrix metalloproteinase synthesis) [44]-may play an alternative or synergistic role in mediating SARS-CoV-2 invasion, although their structural basis is still unknown. It also remains to be seen whether ACE2 expression in other tissues, such as the gastrointestinal tract, kidney, and heart, has similar functions as in the lung.…”
Section: Virologymentioning
confidence: 99%
“…Therefore, the functional interaction between TMPRSS2 and furin is a key factor in determining the level of S protein priming. Other host proteins-such as heat shock protein family A (hsp70) member 5 (HSPA5, also known as GRP78) [43] and CD147 (an inducer of matrix metalloproteinase synthesis) [44]-may play an alternative or synergistic role in mediating SARS-CoV-2 invasion, although their structural basis is still unknown. It also remains to be seen whether ACE2 expression in other tissues, such as the gastrointestinal tract, kidney, and heart, has similar functions as in the lung.…”
Section: Virologymentioning
confidence: 99%
“…Reactive astrocytes also secrete inflammatory cytokines (e.g., IL‐15), which recruit CD8 + T cells and natural killer cells and thereby aggravate the brain lesions (Li et al, 2017; Shi et al, 2020). A recent study using the middle cerebral artery occlusion (MCAO) model suggested that CD147 (EMMPRIN/basigin), an extracellular MMP‐inducer that induces MMP activity and promotes leukocyte extravasation and inflammation (Agrawal & Yong, 2011) is produced by astrocytes during stroke (Patrizz et al, 2020). With regard to the astrocyte endfeet repertoire, Aqp4 expression increases during edema and ischemia.…”
Section: The Gliovascular Interface In Brain Diseasesmentioning
confidence: 99%
“…The release of inflammatory cytokines comes mainly from microglial cells and some researchers have reported that the numbers of cells reached the peak value at 3 days post injury in ICH animal models 23 , 24 . Microglia can be triggered to release pro-inflammatory mediators that are toxic to neurons 25 .…”
Section: Discussionmentioning
confidence: 99%